2018
DOI: 10.1007/s40258-018-0380-z
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Treatment Effect Estimates When Treatment Effects Are Heterogeneous for More Than One Outcome

Abstract: If estimator assumptions are valid, estimates across outcomes can be used to assess the optimality of treatment rates in a study population. However, because true treatment effect parameters are sensitive to correlations of treatment effects across outcomes, decision makers should be cautious about generalizing estimates to other populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(57 citation statements)
references
References 51 publications
(72 reference statements)
2
55
0
Order By: Relevance
“…Instrumental variable methods offer an approach to directly assess this question using populations of Medicare patients with PHF from across local areas. 13,[15][16][17][18][19][20] Our estimates provide evidence to suggest that current PHF surgery rates are higher than the effective surgery rate and that lowering surgery rates may be associated with lower 1-year mortality rates and adverse event risks. These results are especially pronounced for patients with PHF in highrisk patient subgroups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instrumental variable methods offer an approach to directly assess this question using populations of Medicare patients with PHF from across local areas. 13,[15][16][17][18][19][20] Our estimates provide evidence to suggest that current PHF surgery rates are higher than the effective surgery rate and that lowering surgery rates may be associated with lower 1-year mortality rates and adverse event risks. These results are especially pronounced for patients with PHF in highrisk patient subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…21 They are contrasted with risk-adjusted regression (RAR) estimates, which provide information on surgery outcomes for the patients who underwent surgery in our data. 13,[15][16][17][18][19][20] study used deidentified Medicare data. This study follows the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) reporting guideline.…”
Section: Introductionmentioning
confidence: 99%
“…For each subpopulation we tested the association of the measured covariates with ACEI/ARB use and for trends in each covariate across patients grouped by ATR quintiles . Linear 2‐stage least squares (2SLS) IV estimators were used (Data ) . In this study 2SLS yields estimates of the absolute average effect of ACEI/ARBs for the patients whose ACEI/ARB choice was sensitive to local area practice styles or what is known as the local average treatment effect.…”
Section: Methodsmentioning
confidence: 99%
“…Guidelines are based largely on studies of younger patients with well‐preserved renal function, that did not focus on long‐term renal, cardiovascular, or survival outcomes . Observational studies assessing ACEI/ARBs effects using risk‐adjustment approaches have shown mixed results, likely stemming from varying ability to control for confounders and heterogeneity of ACEI/ARB effects across patients …”
Section: Introductionmentioning
confidence: 99%
“…pre-conditions affecting the outcomes) closely related to "real world" are excluded from those studies. 24,25 On the other hand, pragmatic trials are designed to take place in real-world clinical practice settings, where typical patients receive the interventions by clinicians who sometimes did not have any research background. 26 In order to achieve this purpose, pragmatic trials must enroll participants from heterogeneous practice settings, including a broad range of demographic features, to assess several significant outcomes from comparisons involving clinically relevant alternative interventions.…”
Section: Experimental Studies -From Explanatory Rct's To Pragmatic Trmentioning
confidence: 99%